The Role of Experience in Information use and Decision Making by Marketing Managers - Perkins, W. Steven; Rao, Ram C. (Journal of Marketing Research, 1990)
The authors report the results of a study on the use of information and decision making by practicing marketing managers. They examine the effect of managerial experience and decision programmability on managers’ information use and decisions. The results indicate that experience is an important determinant of managers’ behavior for relatively unprogrammed decisions. Moreover, the effects of experience are manifested in the evaluation and use of “soft” information, amount of information used, and the decisions themselves. The authors conclude that in studying the effects of experience on managerial decisions, one must examine the steps leading to a decision; they find that experience affects the prior step in which information is acquired. To the extent experience is a proxy for expertise, the article affords insights into the key ingredients in training and modeling expert managers.